(untitled) (ASEAN Engineering Journal, 2023)
The wave of IR 4.0 has created a competitive environment by transforming the industry in both technical and managerial aspects. Many studies have highlighted the need for a radical shift of conventional design processes in the concept of BIM as a management and collaboration platform. Hence, an effective strategy for the BIM implementation process is needed by developing different BIM capabilities in different cascades of BIM stages. The aim of this study is mainly to investigate BIM capabilities developed by current architectural practices. Six BIM capabilities identified from extensive literature review were Design Authoring, Design Visualisation and Simulation, Design Coordination and Review, Constructability Analysis, Project Changes Management, and Collaboration and Coordination. Each BIM capability were studied according to different BIM activities that must be performed. The The findings revealed different BIM capabilities acquired by the architectural firms in three different BIM stages. For architectural firms in stage 1 BIM implementation, the most acquired BIM capability are Design Authoring, Design Visualisation and Simulation and Constructability Analysis. In BIM stage 2 practices, Constructability Analysis, Collaboration and Coordination, and Design Authoring capabilities were developed. The practices which claimed to be in stage 3 BIM dominated in terms of Design Visualisation and Simulation, Collaboration and Coordination and Design Authoring. The current BIM capabilities will be the basis to suggest critical BIM capabilities that current architectural practices in Malaysia should seek.